Success Rate of Urogenital Fistula Repair and Predictors of Success-An Audit of Ten Years Data - Tasnim, Nasira; Bangash, Kauser; Amin, Oreekah; Batool, Afshan; Javed, Nosheela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate the association of various predictive factors with the outcome of surgical repair of vesicovaginal fistula. Methods: The retrospective analysis was conducted at Maternal and Child Health, Pakistan Institute of Medical Sciences, Islamabad, and it comprised data related to patients having undergone vesicovaginal fistula repair from January 2008 to June 2018. Statistical analysis of the record was done using SPSS 21 software. Results: A total of 364 patients of urogenital fistula repair were reviewed, with an overall success in 318 (87.4%) cases. There were no significant differences in fistula duration (p0.4), size of fistula (p 0.34) and accessibility (p0.5) between successful and unsuccessful group. However, we found the association between the type of fistula and history of previous repair attempts with the success of fistula repair. Primary surgical repair of vesicovaginal (90.0%), vesicouterine (86%), ureteric (100%) and ureterovaginal (98%) were more successful as compared to repair with the history of 1 previous attempt (90.3%, 83.3%, 66.6% and 75% respectively). Success rate was found to further decrease with the history of more than one repair attempt of vesicovaginal (71.4%) and vesicouterine (66.5%) fistula. Further, successful fistula repair in women was also found to be significantly associated with parity less than 4 (p 0.038). Conclusion: Despite the higher success rate of urogenital fistula repair, it’s important to refer the urogenital fistula patients timely to specialized fistula centres in order to achieve best results.